2012
DOI: 10.1007/s10616-012-9443-4
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and characterization of putative mesenchymal stem cells from the spiny mouse

Abstract: The bone marrow represents the most common source from which to isolate mesenchymal stem cells (MSCs). MSCs are capable of differentiating into tissues of the three primary lineages and have the potential to enhance repair in damaged organs through the principals of regenerative medicine. Given the ease with which MSCs may be isolated from different species the aim of this study was to isolate and characterize putative bone marrow derived MSCs from the spiny mouse, Acomys cahirinus. MSCs were isolated from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Also, isolated MSCs from three different sources (bone marrow, synovial membrane and adipose tissue) expressed CD44 and MHC-I [17], while using mouse antibodies, no expression of CD73, CD90 and CD105 was seen in Ovine endometrial MSCs [18]. In a study by Grzesiak et al [19] in which human antibodies were used, ovine adipose derived MSCs showed low expression of CD90 and CD105; isolated bone-marrow and adipose tissue MSCs from Balb/c, C3H and C5BL/6 mice were positive for CD29, CD44, CD105 and Sca-1, but negative for CD34, TER-119, CD45, and CD11b [20]; mouse BM-MSCs were positive for CD44, CD29, CD31, CD44, CD41, CD105 and SCA-1,and negative for CD45, CD3e, CD34, CD45 and CD117 [21]. Additionally, immunophenotypic analysis demonstrated that murine epiphysis derived mesenchymal stem cells were positive for CD29, CD44, CD73, CD105, CD166, Sca-1 and SSEA-4, and negative for CD31, CD34, CD11b and CD45 [22].…”
Section: Discussionmentioning
confidence: 98%
“…Also, isolated MSCs from three different sources (bone marrow, synovial membrane and adipose tissue) expressed CD44 and MHC-I [17], while using mouse antibodies, no expression of CD73, CD90 and CD105 was seen in Ovine endometrial MSCs [18]. In a study by Grzesiak et al [19] in which human antibodies were used, ovine adipose derived MSCs showed low expression of CD90 and CD105; isolated bone-marrow and adipose tissue MSCs from Balb/c, C3H and C5BL/6 mice were positive for CD29, CD44, CD105 and Sca-1, but negative for CD34, TER-119, CD45, and CD11b [20]; mouse BM-MSCs were positive for CD44, CD29, CD31, CD44, CD41, CD105 and SCA-1,and negative for CD45, CD3e, CD34, CD45 and CD117 [21]. Additionally, immunophenotypic analysis demonstrated that murine epiphysis derived mesenchymal stem cells were positive for CD29, CD44, CD73, CD105, CD166, Sca-1 and SSEA-4, and negative for CD31, CD34, CD11b and CD45 [22].…”
Section: Discussionmentioning
confidence: 98%
“…Stem cell identification through the genotypic approach using specific primers is known as the polymerase chain reaction approach. In preparing the stem stage, the expression of negative CD45 and positive CD73, CD90, and CD105 was characterized to ensure that the stem cells inserted were mesenchymal [14][15][16][17][18].…”
Section: The Production Of Bone Marrow Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Fresh bone marrow-derived mesenchymal stem cells (BM-MSCs) were isolated from 4-week-old C57BL/6 mice according to previous publication [ 24 ]. Briefly, bone marrow was flushed out with a syringe and needle, and cultured in Dulbecco's modified Eagle medium (DMEM) supplemented with 10% FBS and 1% penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%